2014
DOI: 10.1377/hlthaff.2014.0534
|View full text |Cite
|
Sign up to set email alerts
|

Early Elective Deliveries Accounted For Nearly 9 Percent Of Births Paid For By Medicaid

Abstract: Reducing early elective deliveries has become a priority for Medicaid medical directors and their state partners. Such deliveries lead to poor health outcomes for newborns and their mothers and generate additional costs for patients, providers, and Medicaid, which pays for up to 48 percent of all births in the United States each year. Early elective deliveries are non-medically indicated labor inductions or cesarean deliveries of infants with a confirmed gestational age of less than thirty-nine weeks. This ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Our primary outcome variable was whether an individual birth was an EED, which we measured using the approach created by Fowler and followed by Dahlen et al We defined an EED as any birth in which a woman was induced into labor or had a Cesarean birth between 37 and 39 weeks of pregnancy without medical justification. The medically justified list includes conditions present throughout the pregnancy such as diabetes, hypertension, eclampsia, breech, and other pregnancy abnormalities, as well as medical conditions present at the time of delivery like premature rupture of membranes, prolonged labor and fetal distress listed in Table .…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Our primary outcome variable was whether an individual birth was an EED, which we measured using the approach created by Fowler and followed by Dahlen et al We defined an EED as any birth in which a woman was induced into labor or had a Cesarean birth between 37 and 39 weeks of pregnancy without medical justification. The medically justified list includes conditions present throughout the pregnancy such as diabetes, hypertension, eclampsia, breech, and other pregnancy abnormalities, as well as medical conditions present at the time of delivery like premature rupture of membranes, prolonged labor and fetal distress listed in Table .…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…These grants, which are distributed by the Center for Medicare and Medicaid Innovation, have the potential to affect a large number of births in the United States; Medicaid paid for just over 44 percent of births in the United States in 2010, and Fowler et al. () found that nearly 9 percent of Medicaid births from 2010 to 2012 were EED. Even before the Strong Start initiative, states had been working to curtail early term births, as infants born early term are more likely to be admitted to the NICU and therefore have higher costs.…”
Section: Policy Efforts To Reduce Early Elective Deliveriesmentioning
confidence: 99%
“…A few recent studies have considered the effects of EED policies on EED rates and on infant health for smaller‐scale programs or for narrower slices of the population. For example, research has shown that hospital‐level policies (Clark et al., ) or changes in Medicaid reimbursement (Fowler et al., ) can effectively reduce early term births in targeted settings. In concurrent work, Byanova () and Dahlen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Medicare and Medicaid Services supported state Medicaid medical directors in a project to track recent trends in early elective deliveries and birth outcomes across states and to review the cost of early elective deliveries to Medicaid based on hospital stays. 6 From 2010 to 2012, approximately 9% of Medicaid singleton deliveries among the 22 participating states were early elective deliveries. In twelve of these states, early-term elective deliveries declined by 32% between 2007 and 2011, a time period reflecting national declines in early elective deliveries across all payers.…”
Section: Multistate Quality-improvement Projectsmentioning
confidence: 99%